The growing applications of click chemistry - Moses, John E; Moorhouse, Adam D (Chemical Society reviews, 2007)
Click chemistry, the subject of this tutorial review, is a modular synthetic approach towards the assembly of new molecular entities. This powerful strategy relies mainly upon the construction of carbon-heteroatom bonds using spring-loaded reactants. Its growing number of applications are found in nearly all areas of modern chemistry from drug discovery to materials science. The copper(I)-catalysed 1,2,3-triazole forming reaction between azides and terminal alkynes has become the gold standard of click chemistry due to its reliability, specificity and biocompatibility.